PENGARUH EKSPOR KOMODITAS PERIKANAN TERHADAP PEREKONOMIAN INDONESIA - Ramadhani, Alisa Sandrina (Media Riset Bisnis Ekonomi Sains dan Terapan, 2024)
This study was conducted to determine whether the export of fishery commodities affected the national economy. In this study, the X variable used is the export value of fishery commodities and the export volume of fishery commodities. Meanwhile, the Y variable used is the Indonesian economy, whose variable measurement uses the value of gross domestic product (GDP). Research was conducted using a method of literature study and simple regression analysis. Research results show that the export value of fishery commodities has a significant effect on the national economy with an R Square value of 0.784 points. Meanwhile, the export volume of fishery commodities also affects the national economy with a value of R Square of 0.730.Keywords: exports, fishery commodities, economy